Response to comments “ Prevalence and clinical predictors of sleep disturbances in children with seasonal allergic rhinitis” - Funda Aytekin Güvenir; Enes Kaan Kılıç; Aslı Kuzu Kuşaklı; Tülay Tuğçe Kutsal Gültekin; Zeynep Şangül Emeksiz; Emine Dibek Mısırlıoğlu (Turkish Journal of Pediatric Disease, 2026)
We sincerely thank the authors for their thoughtful comments and for their interest in our article entitled “Prevalence and Clinical Predictors of Sleep Disturbances in Children with Seasonal Allergic Rhinitis.” We appreciate their constructive observations, which provide an opportunity to further clarify the interpretation of our findings. The authors raise an important methodological point regarding the potential conceptual overlap between the Allergic Rhinitis and its Impact on Asthma (ARIA) severity classification and the Sleep Disturbance Scale for Children (SDSC). We agree that impaired sleep is one of the components considered when classifying allergic rhinitis as moderate-to-severe according to the ARIA guidelines, and therefore some degree of overlap between disease severity and sleep outcomes is theoretically possible. Regarding the specific question of how many children fulfilled the moderate-to-severe ARIA classification solely because of sleep impairment, this information was unfortunately not available, as we evaluated only the overall ARIA severity classification and did not record the individual criteria contributing to disease severity separately. We agree that evaluating disease severity after excluding the sleep-related criterion would represent a valuable methodological approach and could further clarify this relationship in future studies. The authors also appropriately emphasize that pediatric sleep health is influenced by multiple biological, behavioral, familial, environmental, and developmental factors. We fully agree with this broader perspective. Variables such as screen exposure, physical activity, bedtime routines, and sleep hygiene were not systematically collected, as they were beyond the predefined scope of our study, which primarily focused on the relationship between allergic disease characteristics and sleep disturbances. We acknowledge that these factors may influence sleep quality independently or interact with allergic symptoms, and their inclusion in future prospective studies would provide a more comprehensive understanding of sleep health in children with seasonal allergic rhinitis. Similarly, we appreciate the authors’ comments regarding the broad age range of our study population. We agree that sleep characteristics and their determinants may differ between school-aged children and adolescents owing to developmental and behavioral changes. Participants aged 6–16 years were included in the study because the assessment tool used has been validated for this age range. Furthermore, 78 of the 115 participants (67.8%) were aged 10 years or older, indicating that the study population predominantly consisted of older children and adolescents. Although age was recorded as a demographic variable, age-stratified analyses were not prespecified in our study, and the age groups were therefore not analyzed separately. We believe that future studies specifically designed to evaluate developmental differences across age groups would provide valuable additional insight into the relationship between allergic rhinitis and sleep disturbances. Once again, we thank the authors for their insightful comments and for highlighting important considerations regarding the interpretation of pediatric sleep research. We believe these observations complement our findings and further emphasize the importance of adopting a comprehensive approach when evaluating sleep health in children with seasonal allergic rhinitis.